A Panel of CircRNAs in the Serum Serves as Biomarkers for Mycobacterium tuberculosis Infection - Liu, Hengjun; Lu, Geng; Wang, Weixiang; Jiang, Xinrui; Gu, Shuangshuang; Wang, Jin; Yan, Xin; He, Fei; Wang, Jun (Frontiers in Microbiology, 2020)
Tuberculosis (TB), one of the ancient and deadliest diseases, is a chronic immune disorder caused by Mycobacterium tuberculosis (Mtb) infection. Due to the lack of ideal diagnostic and therapeutic markers, TB is still posing a major health, social, and economic burden worldwide. Circular RNA (circRNA), a newly discovered endogenous RNA, is abundant and stable in the cytoplasm and has tissue specificity. More and more studies suggested circRNA is involved in a variety of human pathological and physiological processes. Recently, several studies have confirmed circRNAs not only existed in the serum but also could serve as ideal biomarkers for detecting diseases since the circRNAs have continuous, stable, and covalently closed circular structures and are not easily degraded by nucleases. In this study, we screened the circRNA expression profiles in active TB serum samples and healthy volunteers serum samples by circRNA microarrays. Then, we performed qRT-PCR to verified the dysregulated circRNAs and ROC curve analysis to evaluate the value of circRNAs for TB diagnosis. The results showed circRNA_051239, circRNA_029965, and circRNA_404022 could serve as biomarkers for TB diagnosis.